Shifts in American strategic perception “The geostrategic importance of the Eastern European region” a case study (قضايا سياسية, 2024)
The research aims to elocidate the depth of American strategic perception regarding the significance of Eastern Europe. This is particularly relevant after the shifts that occurred in this perception. Following the dissolution of the Soviet Union, the United States found itself as the sole superpower, a unique position not previously held by any nation since the Peace of Westphalia and the emergence of nation-states. Even in the post-Cold War era, the United States continues to outpace all other countries in the geopolitical system. The research underscores the importance of Eastern Europe as a geostrategic sphere of influence for the United States. However, the central issue it addresses is how America, through its new theoretical propositions, justifies its presence and dominance in the face of ambitious rising revisionist powers, especially the Russian Federation, which possesses historical and demographic roots in this region. The research hypothesis is grounded in the geo-military, economic, and political significance of this area, analyzed through various methodologies. The study is divided into two main axes, in addition to the introduction and conclusion. The first axis discusses the theoretical justifications for American unilateralism and dominance, emphasizing the geostrategic importance of Eastern Europe. The second axis delves into the geostrategic significance of Eastern Europe in American perception.